2005
DOI: 10.1287/mksc.1040.0098
|View full text |Cite
|
Sign up to set email alerts
|

“Counting Your Customers” the Easy Way: An Alternative to the Pareto/NBD Model

Abstract: "Counting Your Customers" the Easy Way: An Alternative to the Pareto/NBD ModelToday's managers are very interested in predicting the future purchasing patterns of their customers, which can then serve as an input into "lifetime value" calculations. Among the models that provide such capabilities, the Pareto/NBD "Counting Your Customers" framework proposed by Schmittlein, Morrison, and Colombo (1987) is highly regarded. But despite the respect it has earned, it has proven to be a difficult model to implement, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
251
0
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(262 citation statements)
references
References 16 publications
0
251
0
11
Order By: Relevance
“…The marketing literature abounds of conceptual [6,7], methodological [13,14] and empirical [15,16] studies of customers' LTV. Methodologically, most empirical contributions are routed in stochastic models of customer behavior [10,14,16] or regression approaches [15,17].…”
Section: Predicting Ltv In Non-contractual Freemium Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The marketing literature abounds of conceptual [6,7], methodological [13,14] and empirical [15,16] studies of customers' LTV. Methodologically, most empirical contributions are routed in stochastic models of customer behavior [10,14,16] or regression approaches [15,17].…”
Section: Predicting Ltv In Non-contractual Freemium Settingsmentioning
confidence: 99%
“…Methodologically, most empirical contributions are routed in stochastic models of customer behavior [10,14,16] or regression approaches [15,17]. The datasets at use mostly describe monetary transactions of customers.…”
Section: Predicting Ltv In Non-contractual Freemium Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, λ and μ follow independent gamma distributions, which are formulated as a mixture distribution model. Although their work is highly regarded and follow-up research has been conducted (Fader, Hardie, andLee 2005a, 2005b;Reinartz andKumar 2000, 2003;Schmittlen and Peterson 1994), it is the increasing importance of new types of marketing, such as Database Marketing, CRM, and One-to-One Marketing, that has brought this model to the attention of researchers and practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…The negative binomial distribution (NBD) model by Ehrenberg (1959) was the starting point for modelling the repeated purchase behaviour. One of the first references proposing a NBD model is the work by Schmittlein et al (1987); extensions and empirical validations of this model can be found in Schmittlein & Peterson (1994) or Fader et al (2005), while applications can be found for example in Reinartz & Kumar (2000, 2003 and Hopmann & Thede (2005). Also with a stochastic approach, Netzer et al (2008) apply a Hidden Markov model in order to capture the dynamics of the behaviour of the customers (donors of several universities).…”
Section: Previous Definitions Of Churn In Non-contractual Settingsmentioning
confidence: 99%